The Former Courier Station. (3rd July 2021) - Xue, Yiwei; Perrow, Betty
Abstract : The story of Xue Yiwei's "The Former Courier Station" ("Yizhan") was based on the writer's real-life experience of escorting his grandmother to visit her hometown in Ningxiang County of Hunan Province in the late 1980s. Xue wrote many short stories that explore the meaning of life and death during this time, and "The Former Courier Station" is one of the representative pieces. It was originally published in the supplement of the United Daily News in Taiwan and later collected in Xue's anthology The Dolphin That Won't Leave ( Buken liqu de haitun ), published by Shanghai Literature and Art Publishing House in 2012.